Pengujian Nuklir (Rudal Balistik) Oleh Korea Utara Menurut Perspektif Hukum Internasional - Putri Anggineysia Bangsa; Josina Augustina Yvonne Wattimena; Johanis Steny Franco Peilouw (Faculty of Law, Universitas Pattimura, 2023)
Introduction: The nuclear tests (ballistic missiles) carried out by that country are in fact contrary to a number of international legal instruments.Purposes of the Research: To know and understand the regulations regarding nuclear (ballistic missiles) in international law and to see in general that North Korea's nuclear test (ballistic missiles) actions are contrary to international law. Methods of the Research: This study uses a normative juridical research type with a descriptive analysis type of research which in the problem approach uses a law, conceptual and case approach with primary, secondary and tertiary legal materials which are then used qualitative analysis techniques.Results of the Research: The act of nuclear testing (ballistic missiles) is actually a form that is not prohibited under international law. However, the intended nuclear test is not carried out arbitrarily but must be in accordance with the instrument or basis for the testing arrangement. Tracing and analyzing the testing actions carried out by North Korea turned out to be contrary to international law where based on every resolution sanctioned by the United Nations Security Council, they wanted to be part of a series of contradictory actions. Apart from that, based on the 1945 United Nations Charter and the 1968 Treaty on the Non-Proliferation of Nuclear Weapons in article VI, it also provides a description of the actions by the North Korean State which indeed violate international law.